2020
DOI: 10.1111/acel.13180
|View full text |Cite
|
Sign up to set email alerts
|

Impaired phagocytic function in CX3CR1+ tissue‐resident skeletal muscle macrophages prevents muscle recovery after influenza A virus‐induced pneumonia in old mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…GM-CSF also plays an important role in the host response to influenza A infection; transgenic expression of Csf2 in mice accelerates viral clearance and attenuates lung injury after influenza A infection, and genetic loss of Csf2 results in more severe lung injury (25)(26)(27). In a murine model of influenza A pneumonia, we reported that, although viral clearance was similar in young adult and aged mice, older mice showed enhanced mortality and worsened lung injury when compared with young adult mice (28). We found that GM-CSF administered intratracheally to mice 1 day before influenza A infection reduced mortality in both young and aged mice (Figure 5, A and B, and Supplemental Figure 5, A and B).…”
Section: Resultsmentioning
confidence: 94%
“…GM-CSF also plays an important role in the host response to influenza A infection; transgenic expression of Csf2 in mice accelerates viral clearance and attenuates lung injury after influenza A infection, and genetic loss of Csf2 results in more severe lung injury (25)(26)(27). In a murine model of influenza A pneumonia, we reported that, although viral clearance was similar in young adult and aged mice, older mice showed enhanced mortality and worsened lung injury when compared with young adult mice (28). We found that GM-CSF administered intratracheally to mice 1 day before influenza A infection reduced mortality in both young and aged mice (Figure 5, A and B, and Supplemental Figure 5, A and B).…”
Section: Resultsmentioning
confidence: 94%
“…All tissues and cells were immediately frozen on dry ice and stored at −80 °C for processing. Muscle satellite cells were prepared as described in work by Runyan et al 74 .…”
Section: Statistics and Reproducibilitymentioning
confidence: 99%
“…Another recently described systemic effect of CX3CR1 is dead cell disposal. An experiment addressing muscle cell death induced by influenza virus infection demonstrates that CX3CR1+ cells are required for phagocytic disposal (Runyan et al 2020). Similarly, phagocytic disposal was impaired in 20-24 months old aged mice.…”
Section: Systemic Cx3cr1 + Effects With Potential Impact On Kidney Diseasementioning
confidence: 99%